Correlation of glenohumeral internal rotation deficit with shoulder pain in elite table tennis players - Zhang, B.; Wang, K.; Zhang, E.; Shang, X. (American Journal of Physical Medicine & Rehabilitation, 2023)
Objective : (1) To investigate glenohumeral internal rotation deficit (GIRD: a difference in internal rotation of 15.6° or more between dominant and nondominant shoulders) and its correlation with self-reported shoulder pain in table tennis players. (2) To find the optimal cutoff point for the difference in the internal rotation (IR) range of motion (ROM) between dominant and nondominant shoulders of self-reported shoulder pain. Design : The IR ROM of both shoulders of 46 table tennis players was measured in the supine and side-lying positions, the external rotation ROM was measured in the supine position. Results : Significant differences existed in IR ROM between the two sides in the supine (z = 6.53, p < 0.001) and side-lying positions (z = 5.67, p < 0.001). Self-reported shoulder pain was associated with GIRD (OR = 6.86, 95% CI: 1.752-26.832, P = 0.006). The cutoff points for the difference in IR ROM between the sides of self-reported shoulder pain were 17.9° in the supine position and 11.1° in the side-lying position. Conclusions : Table tennis players exhibited GIRD. There was a correlation between GIRD and self-reported shoulder pain in the past year; therefore, GIRD may be a risk factor for shoulder pain in table tennis players.